Beyond the Moral Status of the Fetus - Shanley, Mary L. (The Hastings Center report, 1985)
Book reviewed in this article: Abortion and Woman's Choice: The State, Sexuality, and Reproductive Freedom. By Rosalind P. Petchesky. Abortion and the Politics of Motherhood. By Kristin Luker.